Balancing inflammation: the specific roles of serum amyloid A proteins in sterile and infectious diseasese - Tirthankar Mohanty; Katarina Miličević; Henri Göthert; Andreas Tillmann; Médea Padra; Praveen Papareddy; Heiko Herwald (Frontiers in Immunology)
Serum Amyloid A (SAA) proteins are acute-phase reactants with critical roles in sterile and bacterial inflammation. Through in vitro and in vivo experiments, we demonstrate that SAA proteins amplify cytokine and chemokine responses during sterile inflammation and enhance bacterial clearance in infectious conditions. Mechanistically, SAA proteins augment NF-κB signaling, driving pro and anti-inflammatory mediator production. SAA-/- mice carrying a deletion of the Saa1, Saa2, Saa3, and Saa4 serum amyloid A genes have better survival rates in sterile sepsis but are more prone to bacterial sepsis than their SAA+/+ counterparts, emphasizing their dual functionality in immune regulation. Overexpression of Saa1, Saa2, Saa3, and Saa4 in macrophages enhances NF-κB-mediated pro-inflammatory cytokine production and bacterial clearance during infection. Together, our results show that SAA proteins are key modulators of inflammation, with distinct mechanisms tailored to sterile and infectious contexts.